Pengaruh Kelayakan Finansial Terhadap Kesejahteraan Kelompok Tani Berbasis Program Unit Pengolah Pupuk Organik (UPPO) Di Kabupaten Madiun - Silvia Andress Andress; Sumarji Sumarji; Ratna Dewi Mulyaningtiyas (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2023)
The Organic Fertilizer Processing Unit (UPPO) is an effort to improve land fertility to increase agricultural productivity. This study aims to analyze the effect of financial feasibility on the welfare of farmer groups based on the organic fertilizer processing unit (UPPO) program in Madiun Regency. This research is a mixed method research that combines qualitative and quantitative designs at one time. Taking respondents purposively (intentionally) namely 75 people. The location of this research is in Madiun Regency, in 3 sub-districts in the sub-districts of Wonoasri, Mejayan and Saradan. The data collection instrument used a questionnaire instrument. Data Analysis of data using regression analysis and business feasibility (fixed and variable costs, revenue, income, R/C). The results of this study indicate that the Farmer Groups in the Districts of Wonoasri, Mejayan, and Saradan have an R/C Ratio value of > 1, so that a business based on the UPPO program is declared feasible to continue. There is a significant effect of financial feasibility on the welfare of farmer groups in Madiun Regency with a p-value = 0.010.